Invitro Efficacy of Different Chemical Fungicides against Fusarium Spp. in Potato - Shrestha, Rasmita; Shrestha, Subeksha; Sedhai, Adrina; Kapali, Sarita (Nepalese Journal of Agricultural Sciences, 2026)
This study was carried out at the National Plant Pathology Research Center (NPPRC), Khumaltar, Lalitpur to evaluate the efficacy of different chemical fungicides against Fusarium spp. causing dry rot in potato (Solanum tuberosum L.) leading to considerable post-harvest losses. The experiment was conducted using the poisoned food technique in PDA media under laboratory condition. Five fungicides including Samradhi (Mancozeb 75% WP), Nativo (Tebuconazole 50% + Trifloxystrobin 25% WG), M-Control (Chlorothalonil 75% WP), G-Tuphan (Dimethomorph 50% WDG) and Sectin (Fenamidone 10% + Mancozeb 50% WDG) were tested at concentrations of 50 ppm, 100 ppm and 200 ppm in a Completely Randomized Design with four replications. Findings revealed that all fungicides inhibited the mycelial growth of Fusarium spp., with variations among concentrations and observation days. Samradhi (Mancozeb 75% WP) and Nativo (Tebuconazole 50% + Trifloxystrobin 25% WG) were the most effective fungicides, providing 100% mycelial inhibition from day 1 to day 5 at all concentrations tested. Moderate inhibition was recorded with M-Control (Chlorothalonil 75% WP), ranging from 51.31% at 50 ppm on day 1 to 61.70% at 200 ppm on day 5. G-Tuphan (Dimethomorph 50% WDG) also showed moderate suppression, increasing from 35.20% at 50 ppm on day 1 to 59.62% at 200 ppm on day 5. Sectin (Fenamidone 10% + Mancozeb 50% WDG) showed the lowest efficacy, with inhibition values ranging from 34.21% at 50 ppm on day 1 to 47.32% at 200 ppm on day 5. The results indicate that Samradhi (Mancozeb 75% WP) and Nativo (Tebuconazole 50% + Trifloxystrobin 25% WG) are highly effective in suppressing Fusarium spp. under laboratory conditions. Field-level validation is essential before recommending these fungicides for integration into potato dry rot management practices.